DAMPAK EKONOMI KEBIJAKAN PARIWISATA RECEP TAYYIB ERDOGAN PADA TAHUN 2003-2011 DAN 2014 DI TURKI - Moddie Alvianto Wicaksono (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
As a country that located in two regions, Middle East and Europe, Turkey has a tourism sector attraction. Starting from it nature tourism, history, and culture. Under Reccep Tayyib Erdogan leadership, Turkey tourism becomes a main country’s income. It is in line with that Turkey tourism is pioneer of friendly Moslem tourism destination. This study aims to determine Turkey tourism policy and to discover it’s impact under Erdogan era, especially in 2003-2011. By using public policy theory of David Easton and tourism concept of Edgell, the researcher knows that Erdogan has a capabilty to explore natural, historical and cultural side of turkey tourism. The amount of income is increasing and it is also incrases Erdogan’s prestige as a leader. With qualitative-explanatory research and literature studies, the researcher took a sample of Turkey tourism data from 2011 until 2015. The result of this study is that Turkey opens up a great job opportunities and ables to increase DGP by strengthening the tourism sector.